Hak Asasi Perempuan dalam Peraturan Perundang-Undangan Di Indonesia - Dede Kania (Jurnal Konstitusi, 2015)
Up to now, the law is still considered discriminatory and gender inequality. Though the law should be equal or sensitive to gender inequality to guarantee women’s rights. By following the principle of equality in all areas of the good men  and women have equal rights or opportunities to participate in every aspect of social life and state. so if there is discrimination against women, it is a violation of women’s rights. women’s rights violations occur due to many things, including the result of the legal system, where women are victims of the system. Reform Order is the most progressive period in the protection of human rights. Various laws and regulations come outin this period, including laws and regulations concerning women’s rights. Seen from the government’s efforts to eliminate discrimination based on sex are included in many  legislations.